Neurodevelopmental outcomes in children with cyanotic congenital heart disease following open heart surgery - Samir Shakya; Anita Saxena; Sheffali Gulati; Shyam Sunder Kothari; Sivasubramanian Ramakrishnan; Saurabh Kumar Gupta; Velayoudam Devagourou; Sachin Talwar; Palleti Rajashekar; Shobha Sharma (Wolters Kluwer Medknow Publications, 2022)
Background : Neurodevelopmental abnormalities are common in congenital heart disease (CHD), more so in cyanotic CHDs. Perioperative factors have been known to affect neurodevelopmental outcomes. Aim : We aimed to determine the neurodevelopmental outcomes following open-heart surgery in cyanotic CHD. Methods : In this prospective observational study, eligible infants and children ≤21 months with cyanotic CHD planned for open-heart surgery underwent preoperative neurodevelopmental assessment using Developmental Assessment Scale for Indian Infants (DASII) to look for any motor and/or mental delay. A second neurodevelopmental assessment was performed after 9 months ± 2 weeks of cardiac surgery. Follow-up DASII was conducted through interactive video conferencing in 23 of 60 patients due to COVID-19 pandemic. The univentricular and biventricular repair groups were compared in terms of their neurodevelopmental outcomes. Perioperative factors were compared between neurodevelopmental "delay" and "no delay" groups. Results : Of the 89 children enrolled, preoperative motor and mental delay were present in 29 and 24 children, respectively. Follow-up DASII could be performed in 60 children. At follow-up, motor delay was present in seven and mental delay in four children. Overall, there was a significant improvement in both motor and mental developmental quotient at follow-up. There was no significant difference in either motor or mental domains between univentricular and biventricular groups. Among the perioperative variables, only the postoperative length of stay in intensive care unit was significantly different between neurodevelopmental "delay" and "no delay" groups (P = 0.04). Conclusion : Neurodevelopmental delay occurred substantially among unoperated children with cyanotic CHD. The neurodevelopmental status improved significantly following open-heart surgery among the survivors. Delay was associated with length of stay in intensive care following cardiac surgery.